Impacts of ultraviolet radiation on certain physiological and biochemical processes in cyanobacteria inhabiting diverse habitats - Rajneesh; Pathak, Jainendra; Richa; Häder, Donat-Peter; Sinha, Rajeshwar P. (Environmental and Experimental Botany, 2019)
Certain physiological and biochemical processes of Fischerella sp. strain HKAR-13 and Nostoc sp. strain HKAR-2 isolated from paddy field and hot spring respectively were studied in response to ultraviolet radiation (UVR). Cultures were irradiated under varying combinations of UV-B, UV-A and photosynthetically active radiation (PAR). Significant decrease in chlorophyll a content was observed in Nostoc sp. strain HKAR-2 (19.31 to 4.08 mu g/gfw) and Fischerella sp. strain HKAR-13 (13.55 to 3.40 mu g/gfw) after 72 h of PAR + UV-A + UV-B (PAB) treatment. Total carotene content increased upto 36 h where as phycocyanin content decreased as exposure time increased in both the cyanobacteria. Photosystem II (PSII) activity decreased to about 88% and 93% in Nostoc sp. strain HKAR-2 and Fischerella sp. strain HKAR-13 respectively. Antioxidative activities of superoxide dismutase and catalase increased to 1.8-6.0 fold after 48 h of UVR exposure as compared to non-irradiated cultures. Additionally, Fischerella sp. strain HKAR-13 was also able to synthesize scytonemin that carry out UV-screening but its synthesis was not observed in Nostoc sp. strain HKAR-2. UVR also resulted in 3-5 fold increase in reactive oxygen species in Fischerella sp. strain HKAR-13 and 2.0-4.5 fold increase in Nostoc sp. strain HKAR-2. Significant decrease in ds DNA content and increase in malondialdehyde content was observed in both cyano-bacterial strains. These results revealed that combined effects of UV-A + UV-B was more deleterious than UV-A and UV-B alone and Fischerella sp. strain HKAR-13 was more prone to UVR as compared to Nostoc sp. strain HKAR-2, a hot spring isolate. The more resistant cyanobacterium Nostoc sp. strain HKAR-2 can be used as inoculant in desert soil and production of various value added products.
CRIS-Team WoS Importer:2019-05-24